Investigating the relationship between epidemiological factors and the prevalence of head lice infestation (Pediculus capitis) in girls\' primary schools in Kabudarahang County - Behroz Davari; Yusuf Alizadeh; Hassan Nasirian; Amir Hossein Zahirnia; Arefeh Salehzadeh; Younes Mohammadi; Bahar Davari (فصلنامه ابن سینا)
Background and aims: Head lice infestation is a global parasitic disease that poses a significant threat to public health and is considered a health priority. This study aimed to investigate the relationship between epidemiological factors and the prevalence of head lice infestation in girls' primary schools in Kabudarahang County. Methods: This observational cross-sectional study was conducted during the academic year 2022-2023. Information on infested students in girls' elementary schools was recorded following identification. The results were analyzed with the Chi-square test. Results: In this study, 1,427 students were examined, and 272 were identified as having head lice infections.The prevalence of head lice infestation was found to be 19.1%. Significant associations were observed with factors such as age, educational levels of parents, number of family members, use of personal combs, bathing frequency per week, and previous disease history (p<0.05). In contrast, hair length, and hair condition did not significantly influence the incidence of head lice. Conclusion: Education of students should be included in the agenda of school health educators. Elevating the literacy levels of both students and parents can significantly improve self-care practices and help prevent head lice infestations.